Analisis Anomali Kebijakan: Prospek terhadap Kualitas Kebijakan - Hermansyah Putra, Dio Fandy; Setyowati, Endah; Hidayati, Firda (Jurnal Ilmiah Administrasi Publik, 2024)
The terminology of policy failure is potentially rejected by the government. Because the consequences of policy failure will have a negative impact on the image of the government itself. The concept of policy failure is a broad and useful concept policy analysis. Policy anomaly is a concept born of policy failure. The aim of this article, to review several research literature related to the concept and indicators of policy anomalies, to clarify the extent and through what mechanisms policy anomalies can be recognized in the public policy process. Several relevant literature related to policy anomalies have been reviewed. Based on the findings article, policy anomalies provide clues to learn from past mistakes by releasing the wrong way in managing and implementing public policies. As well, to understand more effectively the rules and procedures that hinder by focusing on analysis of policy failures. The main emphasis on management, program, and political anomalies analysis, and two dimensions of anomaly: bad formulation and bad implementation. Furthermore, anomaly analysis must address political debates on policy processes, often under-discussed. Because, can help develop an understanding of how governments fail in some ways, but not in other. So the policy solution given will be more targeted.